Correction: The "Histoplasmosis Porto Alegre manifesto"-Addressing disseminated histoplasmosis in AIDS. - PLOS Neglected Tropical Diseases Staff (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pntd.0010960.].